2016
DOI: 10.1111/bcpt.12554
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylcysteine in Acute Organophosphorus Pesticide Poisoning: A Randomized, Clinical Trial

Abstract: Organophosphorus poisoning is a major global health problem with hundreds of thousands of deaths each year. Research interest in N-acetylcysteine has grown among increasing evidence of the role of oxidative stress in organophosphorus poisoning. We aimed to assess the safety and efficacy of N-acetylcysteine as an adjuvant treatment in patients with acute organophosphorus poisoning. This was a randomized, controlled, parallel-group trial on 30 patients suffering from acute organophosphorus poisoning, who were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…N-acetylcysteine (NAC) is an antioxidant compound used in the treatment of acetaminophen overdose, which may also be a useful adjunct to the traditional standard of care after acute OP exposure. In a randomized, controlled, parallel-group clinical trial, intravenous NAC was shown to reduce the amount of atropine required for symptomatic relief after acute organophosphate poisoning (El-Ebiary et al, 2016). Recently it has also been shown that the essential omega-3 polyunsaturated fatty acid alpha-linolenic acid can rescue soman induced behavior deficits in rats and to reduce rates of corresponding cell death in multiple brain regions (Pan et al, 2015).…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…N-acetylcysteine (NAC) is an antioxidant compound used in the treatment of acetaminophen overdose, which may also be a useful adjunct to the traditional standard of care after acute OP exposure. In a randomized, controlled, parallel-group clinical trial, intravenous NAC was shown to reduce the amount of atropine required for symptomatic relief after acute organophosphate poisoning (El-Ebiary et al, 2016). Recently it has also been shown that the essential omega-3 polyunsaturated fatty acid alpha-linolenic acid can rescue soman induced behavior deficits in rats and to reduce rates of corresponding cell death in multiple brain regions (Pan et al, 2015).…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…D) Organophosphate Poisoning: NAC is safe and it can be used as an adjuvant to treatment in patients suffering from organophosphate poisoning, also there is no adverse effects were reported with its use. However, NAC had no significant effect on length of hospitalization and its use may provide an extra benefit through the reduction of atropine requirements and hence the proposed adverse effects resulting from a large dose of atropine used in these cases of poisonings [49]. E) Prevention of Contrast-Induced Nephropathy: one randomized double-blind study shown that oral NAC 600 mg twice daily on the day before and the day of the CT scan compare to placebo indicate that acute renal failure occurred in 21% of placebo subjects compared with 2% in the NAC group.…”
Section: Off Label Uses Of Acetylcysteine (Nac)mentioning
confidence: 94%
“…Furthermore, these substances have remarkable importance for agricultural purposes. For instance, pesticides play an important role in combating the pests that cause damages to agricultural crops so that it is possible to enhance productivity [2]. Despite the important application of these compounds, their toxic effects are extremely harmful to humans, animals, and the environment, with high contamination rates.…”
Section: Introductionmentioning
confidence: 99%